Analisis Pengaruh Penyelesaian Tindak Lanjut Rekomendasi Hasil Pemeriksaan BPK pada Pemerintah Kabupaten dan Kota di Pulau Kalimantan - Mery Mei Lestari; Tina Lestari (Politeknik Ganesha Medan, 2022)
The purpose of this study was to identify and analyze the Factors Affecting the Level of Completion of Follow-Up Recommendations on the Examination Results of the Supreme Audit Agency at the Regency and City Governments on the Island of Kalimantan. This type of research is correlational or finding out the relationship and level of relationship between variables without any attempt to influence these variables. The sampling technique used is purpose sampling.The data analysis method used by the author in this study uses multiple linear regression analysis techniques.The results of this study indicate that there is a significant influence of the auditor's skill factor, the type of local government, dependence on the central government, the term of office of the regional head, DPRD supervision and APIP capability simultaneously on the follow-up to the results of audit recommendations at the Supreme Audit Board of the Regency and City Governments on the island of Kalimantan. . There is a significant effect of the auditor's skill factor, the type of regional government, dependence on the central government and APIP capability partially on the follow-up to the results of the audit recommendations, while the factor of the position of the regional head and DPRD supervision has no partial significant effect on the follow-up to the results of the audit recommendations at the Supreme Audit Agency. to the Regency and City Governments on the island of Kalimantan. APIP capability has a dominant effect on there is no partial significant effect on the follow-up to the results of audit recommendations at the Supreme Audit Agency in Regency and City Governments on the island of Kalimantan.